The Extend of Differentiated Instruction Implementation in Junior High School’s English Subject - Kusasi, Muhammad Aiman Zaidan; Hanifah; Elfiza, Rona (Universitas Maritim Raja Ali Haji (UMRAH), 2025)
The implementation of the Merdeka Curriculum in Indonesia has brought about significant changes in the educational landscape, particularly through the introduction of Differentiated Instruction. This qualitative descriptive research aimed to analyse the implementation of Differentiated Instruction in the English subject at SMP Islam De Green Camp Tanjungpinang, a Sekolah Penggerak for the Merdeka Curriculum. The study focused on exploring English teachers' perceptions of Differentiated Instruction, their understanding of its concept, and the extent to which it was being implemented in their classrooms. The findings revealed that while teachers generally had a positive perception of the Merdeka Curriculum and Differentiated Instruction, their practical implementation was still evolving. Although they understood the theoretical underpinnings of Differentiated Instruction, there were gaps in fully differentiating all four elements of instruction: content, process, product, and learning environment. This research contributes to the understanding of how Differentiated Instruction is being interpreted and applied in the context of the Merdeka Curriculum, highlighting both the progress made and the areas that require further development to fully realize the potential of Differentiated Instruction in enhancing student learning outcomes.